Representasi Belis Sebagai Identitas Budaya Nusa Tenggara Timur dalam Film Nona Manis Sayange - Maria Claudia Inesensia Setu; Kadek Dristiana Dwivayani; Silviana Purwanti; Harry Isra Muhammad (CV. Green Publisher Indonesia, 2026)
This research is entitled Representation of Belis as Cultural Identity of East Nusa Tenggara in the Film Nona Manis Sayange. The background of the research suggests that the belis tradition plays an important role as a marker of cultural identity in East Nusa Tenggara, but also faces social problems including economic burdens, power relations, and gender dimensions that are mediated and represented through film. This research aims to identify and interpret the meaning of belis in the film Nona Manis Sayange 2023. The method used is qualitative with Roland Barthes' semiotic analysis to read signs at three levels of significance (denotation, connotation, and myth), as well as Stuart Hall's representational framework to understand the process of encoding-decoding meaning in the film text. Primary data in the form of selected scenes in a number of key scenes from the film's duration of 1 hour 42 minutes, then analyzed textually and visually. The results show that the film represents belis as a multi-layered phenomenon: denotatively it appears as a traditional ritual that connects families; connotatively it functions as an indicator of social status, economic pressure, and an arena for gender negotiation; at the mythical level, the film provokes discourse that belis can be a determinant of self-esteem and worthiness. However, the film also opens up space for criticism and reinterpretation, showing that belis can be preserved as a cultural heritage while being recontextualized to be more just and humane. The implications of this research recommend that cultural representation in the media be carried out contextually, reflectively, and sensitively to social dynamics.